Normal values for paediatric atrial volumes assessed by steady-state free-precession cardiovascular magnetic resonance. (14th October 2021) - Voges, I; Hinz, S; Caliebe, A; Boroni Gracioli, S; Wage, R; Gabbert, D; Uebing, A; Krupickova, S
Abstract: Background: Measurement of atrial volumes by steady-state free precession (SSFP)cardiovascular magnetic resonance (CMR) is becoming increasingly important in the treatment and follow-up of paediatric congenital heart disease. It has prognostic value in terms of heart failure and cardiovascular death. However, CMR normal values for the clinically often used mono- and biplane area-length method in children are lacking. Aims: We sought to create paediatric normal values for atrial volumes using the mono- and biplane area-length method. Methods: In a retrospective study design, CMR data sets of 157 healthy children with an age range between 4 and 18 years from two centers in the UK and Germany were evaluated. In a four-chamber (4ch-) view, left and right atrial (LA, RA) endocardial borders were segmented during end-diastole and end-systole to calculate minimal and maximal atrial volumes (LAmin, LAmax, RAmin, RAmax) using the monoplane area-length method. Additionally, end-diastolic and end-systolic LA endocardial borders were segmented in a two-chamber (2ch-) view. Using the measurements from the 2ch- and 4ch-views, minimal and maximal LA volumes were calculated using the biplane area-length method. Atrial volumes were normalized for body surface area (BSA in m 2 ). Sex-specific reference curves were created using the lambda mu sigma method. Results: The median age was 13.8±2.81 years (53 girls). In children from 4–10 years average atrial volumes measured: monoplane 4ch: LAmin 10.2±3.5 ml/m 2, LAmax 28.8±7.4 ml/m 2, RAmin 14.1±6.3 ml/m 2, RAmax 27.0±11.4 ml/m 2 ; monoplane 2ch: LAmin 10.9±4.1 ml/m 2, LAmax 27.0±6.1 ml/m 2 ; biplane: LAmin 10.2±3.3 ml/m 2, LAmax 27.4±5.7 ml/m 2 . In children from 11–18 years average atrial volumes measured: monoplane 4ch: LAmin 13.6±4.9 ml/m 2, LAmax 34.1±9.1 ml/m 2, RAmin 19.2±6.8 ml/m 2, RAmax 34.2±9.6 ml/m 2 ; monoplane 2ch: LAmin 13.2±4.9 ml/m 2, LAmax 31.4±9.7 ml/m 2 ; biplane: LAmin 12.9±4.4 ml/m 2, LAmax 31.8±8.8 ml/m 2 . Separate centile charts and centile tables for boys and girls for all volumetric parameters were created. Conclusion: We provide paediatric CMR reference values for atrial volumes. They can be used in the diagnosis and follow-up of congenital or acquired heart disease in children and for research purposes. FUNDunding Acknowledgement: Type of funding sources: None.